Effects of cerebellar transcranial direct current stimulation on rehabilitation of upper limb motor function after stroke - Gong, Qiuwen; Yan, Rubing; Chen, Han; Duan, Xia; Wu, Xiaoyu; Zhang, Xin; Zhou, Yi; Feng, Zhou; Chen, Ya; Liu, Jianbo; Xu, Peng; Qiu, Jing; et al. (Frontiers in Neurology, 2023)
Background The cerebellum is involved in the control and coordination of movements but it remains unclear whether stimulation of the cerebellum could improve the recovery of upper limb motor function. Therefore, this study aimed to explore whether cerebellar transcranial direct current stimulation (tDCS) therapy could promote the recovery of upper limb motor function in patients who suffered a stroke. Methods In this randomized, double-blind, and sham-controlled prospective study, 77 stroke patients were recruited and randomly assigned to the tDCS group (n = 39) or the control group (n = 38). The patients received anodal (2 mA, 20 min) or sham tDCS therapy for 4 weeks. The primary outcome was the change in the Fugl-Meyer Assessment-Upper Extremity (FMA-UE) score from baseline to the first day after 4 weeks of treatment (T1) and 60 days after 4 weeks of treatment (T2). The secondary outcomes were the FMA-UE response rates assessed at T1 and T2. Adverse events (AEs) related to the tDCS treatment were also recorded. Results At T1, the mean FMA-UE score increased by 10.7 points [standard error of the mean (SEM) = 1.4] in the tDCS group and by 5.8 points (SEM = 1.3) in the control group (difference between the two groups was 4.9 points, P = 0.013). At T2, the mean FMA-UE score increased by 18.9 points (SEM = 2.1) in the tDCS group and by 12.7 points (SEM = 2.1) in the control group (the difference between the two groups was 6.2 points, P = 0.043). At T1, 26 (70.3%) patients in the tDCS group had a clinically meaningful response to the FMA-UE score compared to 12 (34.3%) patients in the control group (the difference between the two groups was 36.0%, P =0.002). At T2, 33 (89.2%) patients in the tDCS group had a clinically meaningful response to the FMA-UE score compared with 19 (54.3%) patients in the control group (the difference between the two groups was 34.9%, P = 0.001). There was no statistically significant difference in the incidence of adverse events between the two groups. In the subgroup analysis of different hemiplegic sides, the rehabilitation effect of patients with right hemiplegia was better than that of patients with left hemiplegia (P < 0.05); in the age subgroup analysis, different age groups of patients did not show a significant difference in the rehabilitation effect (P > 0.05). Conclusion Cerebellar tDCS can be used as an effective and safe treatment to promote recovery of upper limb motor function in stroke patients. Trial registration ChiCTR.org.cn, identifier: ChiCTR2200061838.